Analisis Penerapan Akuntansi Pada Usaha Coffee Shop “Sobat Kopi” - Asipah Pauziah; Adinda Putri Lestari; Indah Nabilah Hidayah; MH. Ainulyaqin (JPIES: Jurnal Pelita Ilmu Ekonomi Syariah, 2025)
This study aims to analyze the application of accounting in the Coffee Shop "Sobat Kopi" in Cibitung District. The results of the study show that even though this Coffee Shop has applied basic accounting principles by recording daily transactions using the Qashir application, the financial statements prepared are still not in accordance with applicable accounting standards. Coffe Shop "Sobat Kopi" only compiles profit and loss statements based on the recording of the application and does not have complete financial reports. The main problem faced is the lack of knowledge of business owners about the importance of preparing financial statements in accordance with standards and business management carried out independently by the owner. This study highlights the need to improve business owners' understanding of accounting in order to prepare more complete financial statements in accordance with applicable accounting standards.